2019
DOI: 10.1186/s13046-019-1245-5
|View full text |Cite
|
Sign up to set email alerts
|

New markers for human ovarian cancer that link platinum resistance to the cancer stem cell phenotype and define new therapeutic combinations and diagnostic tools

Abstract: Background Ovarian cancer is the leading cause of gynecologic cancer-related death, due in part to a late diagnosis and a high rate of recurrence. Primary and acquired platinum resistance is related to a low response probability to subsequent lines of treatment and to a poor survival. Therefore, a comprehensive understanding of the mechanisms that drive platinum resistance is urgently needed. Methods We used bioinformatics analysis of public databases and RT-qPCR to qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 48 publications
3
25
0
Order By: Relevance
“…Resistance to antitumoral agents, especially cytotoxicity, has been linked to the presence of CSCs in tumors [42,43]. It is believed that chemotherapy is effective against non-CSC tumor cells but not against CSCs, which are able to initiate new tumor growth after therapy and promote metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to antitumoral agents, especially cytotoxicity, has been linked to the presence of CSCs in tumors [42,43]. It is believed that chemotherapy is effective against non-CSC tumor cells but not against CSCs, which are able to initiate new tumor growth after therapy and promote metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence for C‐KIT cross‐talk with NANOG and OCT4 specifically, is supported by earlier studies which revealed that cisplatin treatment enhances the expression of C‐KIT , NANOG and OCT4 in residual ovarian cancer cells in vitro . Furthermore, inhibition of the NOTCH and C‐KIT/MAPK/MEK pathways in vitro re‐sensitized OCa CSC‐enriched tumorshperes to cisplatin and carboplatin . Based on these lines of evidence, the targeting of stemness pathways has therefore been proposed as a strategy to increase the effectiveness of cancer therapies.…”
Section: Mechanisms Of Platinum Resistance In Ovarian Cancermentioning
confidence: 57%
“…The genes involved in these pathways are often dysregulated in Oca CSC‐LCs, and are usually integrated into three main clusters involving the WNT/ Β‐ CATENIN/NOTCH network, the MEK/MAPK network and the NANOG/SOX2/OCT4/KLF4 network . Interestingly, in Oca patients with platinum‐resistant tumors, these three pathways were found to be interconnected through a fourth pathway involving C‐KIT, STAT3, NOTCH1 and MYC . This evidence for C‐KIT cross‐talk with NANOG and OCT4 specifically, is supported by earlier studies which revealed that cisplatin treatment enhances the expression of C‐KIT , NANOG and OCT4 in residual ovarian cancer cells in vitro .…”
Section: Mechanisms Of Platinum Resistance In Ovarian Cancermentioning
confidence: 97%
See 1 more Smart Citation
“…CSCs and non-CSCs can also interconvert in dynamic equilibrium. Non-CSCs can acquire CSC properties through de-differentiation (8,(22)(23)(24), and in this process, either genetic or epigenetic alterations, as well as microenvironment may be involved (25)(26)(27)(28). Therefore, the CSCs model should be considered to be bidirectional, switching between stem and mature cells within the tumor (8,(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%